2018
DOI: 10.1130/ges01561.1
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic offsets along the creeping Laohu Shan section of the Haiyuan fault, northern Tibetan Plateau

Abstract: High-resolution topographic or imagery data effectively reveal geomorphic offsets along faults that can be used to deduce slipper event of recurrent rupture events. Documentation of patterns of geomorphic offsets is scarce on faults that undergo both creep and coseismic rupture. In this paper, we used newly acquired high-resolution light detection and ranging (LiDAR) data to compile geomorphic offsets along the Laohu Shan section of the Haiyuan fault, in the northern Tibetan Plateau, where interferometric synt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 58 publications
1
39
0
Order By: Relevance
“…There is some evidence for the surface-breaking rupture of paleoearthquakes in this section. In addition, the cumulative slip offset in this region is similar to noncreeping brittle faults (Chen et al, 2018). Based on these observations, Chen et al (2018) inferred that either the fault is capable of switching between creeping and brittle faulting over time or the fault is partially creeping.…”
Section: The Characteristics Of Repeating Earthquakes At the Laohushamentioning
confidence: 79%
See 2 more Smart Citations
“…There is some evidence for the surface-breaking rupture of paleoearthquakes in this section. In addition, the cumulative slip offset in this region is similar to noncreeping brittle faults (Chen et al, 2018). Based on these observations, Chen et al (2018) inferred that either the fault is capable of switching between creeping and brittle faulting over time or the fault is partially creeping.…”
Section: The Characteristics Of Repeating Earthquakes At the Laohushamentioning
confidence: 79%
“…In addition, the cumulative slip offset in this region is similar to noncreeping brittle faults (Chen et al, 2018). Based on these observations, Chen et al (2018) inferred that either the fault is capable of switching between creeping and brittle faulting over time or the fault is partially creeping. In the second possibility, the creep on the Laohushan section is a shallow phenomenon, with the fault remaining locked at depth, similar to the Ismetpasa segment of the North Anatolian fault in Turkey (Kaneko et al, 2013;Karabacak et al, 2011;Ozener et al, 2010) and the Hayward fault in northern California (Schmidt et al, 2005;Simpson et al, 2001).…”
Section: The Characteristics Of Repeating Earthquakes At the Laohushamentioning
confidence: 79%
See 1 more Smart Citation
“…Between major events occurring every 800–1,000 years, moderate magnitude earthquakes also occurred in this section, the recent ones being 20 October 1990 Mw 5.8 Tianzhu earthquake and 2000 Mw 5.6 Jingtai earthquake (Committee for Chinese Earthquake Bulletin, ; Cai et al, ; US Geological Survey National Earthquake Information Center, ). The 35‐km‐long very eastern end of the Laohu Shan section is likely creeping at a rate of ~5 mm/year indicated by the analysis of interferometric synthetic aperture radar data (Cavalié et al, ; Jolivet et al, ), despite that numerous geomorphic offsets of gullies were found to cluster at amounts of sell‐separated increments, similar to the geomorphic offset pattern on noncreeping faults (Chen et al, ).…”
Section: Geologic Settingmentioning
confidence: 92%
“…Liu‐Zeng et al () identified three or four seismic events on the Haiyuan fault since A.D. 1500 based on trench and historical records. In addition, Chen et al () systematically measured offset landforms along the Laohushan fault using lidar data. To the west of the Tianzhu Basin, the slip rates and paleoseismology of the fault segments are much less studied.…”
Section: Geological Settingmentioning
confidence: 99%